2017
DOI: 10.1002/2017gb005669
|View full text |Cite
|
Sign up to set email alerts
|

Eddy‐induced carbon transport across the Antarctic Circumpolar Current

Abstract: The implications of a mesoscale eddy for relevant properties of the Southern Ocean carbon cycle are examined with in situ observations. We explored carbon properties inside a large (~190 km diameter) cyclonic eddy that detached from the Subantarctic Front (SAF) south of Tasmania in March 2016. Based on remote sensing, the eddy was present for ~2 months in the Subantarctic Zone (SAZ), an important region of oceanic carbon dioxide (CO2) uptake throughout the annual cycle and carbon subduction (i.e., where mode a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(65 citation statements)
references
References 80 publications
3
61
1
Order By: Relevance
“…INEs were determined using immersion freezing of aliquots of SW samples (stored frozen) and the IS. Chl a were measured using standard techniques (filtering and acetone extraction, Holm‐Hansen et al, ; Lorenzen, ) with a Turner Trilogy fluorometer (Moreau et al, ). Satellite‐derived ocean color (Moderate Resolution Imaging Spectroradiomete, https://oceandata.sci.gsfc.nasa.gov/MODIS-Aqua) was used to estimate ocean surface Chl a during CAPRICORN.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…INEs were determined using immersion freezing of aliquots of SW samples (stored frozen) and the IS. Chl a were measured using standard techniques (filtering and acetone extraction, Holm‐Hansen et al, ; Lorenzen, ) with a Turner Trilogy fluorometer (Moreau et al, ). Satellite‐derived ocean color (Moderate Resolution Imaging Spectroradiomete, https://oceandata.sci.gsfc.nasa.gov/MODIS-Aqua) was used to estimate ocean surface Chl a during CAPRICORN.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, CAP18 was collected over a region with similar (Frenger et al, 2015) that impact biological productivity by advecting phytoplankton patches or by enhancing or prohibiting upwelling of deep ocean waters containing high nutrients (Gaube et al, 2013). As described by Moreau et al (2017), the cold-core eddy sampled during CAPRICORN developed from the Sub-Antarctic Front and was identified based on negative sea surface height anomalies, with an eddy diameter of approximately 190 km. This cold-core eddy contained low surface Chl a in the eddy center (0.33 mg/m 3 ) with higher surface Chl a at the eddy peripherals (0.74 mg/m 3 ; Moreau et al, 2017).…”
Section: Characteristics Of Inps Observed During Capricornmentioning
confidence: 99%
“…However, the surface water temperature was 7.28C, salinity was 33.8 ( Fig. 5) and nitrate and silicate concentrations were 22 and silicate was 3.3 mM respectively, all typical of polar waters located further south of the northern extension of the SAF (Moreau et al 2017;Patel et al 2019). Satellite analysis revealed that the eddy had formed in early February 2016 and moved northward ,1.28 of latitude at the time of sampling (Patel et al 2019).…”
Section: Hydrographymentioning
confidence: 95%
“…1), with its centre located at ,50.48S, 147.18E. The eddy was ,190 km in diameter and was a stable feature that had formed in mid-February 2016, ,1.28 further south of the sampling site near the SAF (Moreau et al 2017). After formation, the eddy moved slowly northward across the northern extension of the SAF with a rotation speed of 0.527 rad day À1 (Moreau et al 2017;Patel et al 2019).…”
Section: Sampling Sitesmentioning
confidence: 96%
See 1 more Smart Citation